(untitled) (Asian Education Studies, 2017)
This paper discusses the challenges and opportunities to the education sector of the ASEAN Regional Integration launched in 2015. The Philippine education was subjected to reforms and transitions due to the K to 12 Basic Education Enhancement Program of adding two years of Senior High School. Consequently, the Higher Education Institutions suffered setbacks, decrease in enrolment and displacement of teachers. The case of St. Paul University Philippines portrays the educational strategies and activities of meeting these challenges and taking advantage of the opportunities at hand. Of foremost consideration to the successful experience of SPUP are its internationalization program, the convergence of cultural and religious differences, and the citizenship and character components of its Paulinian education. These were supported by policy and organizational structures, curriculum reviews, new learning modalities, international partnerships and linkages, global learning, and practice of inter-cultural competence. The internationalization of SPUP is a positive response to the ASEAN Integration.